Preparation, characterization, and anticancer effect of Capsaicin-functionalized selenium nanoparticles - Tang, Enhui; Ma, Ziqing; Zhang, Peiting; Chen, Yuyang; Zhou, Yiman; Wu, Jieying; Yang, Tingting; Lian, Duanya; Wu, Xinlan (Frontiers in Nutrition, 2024)
IntroductionSelenium nanoparticles (SeNPs) are recently emerging as promising anticancer agents because of their high bioavailability, low toxicity and remarkable anticancer activities. However, the application of SeNPs in anticancer has been limited due to instability. Herein, Capsaicin (Cap), a natural active compound found in chili peppers with favorable anticancer activity, was modified with SeNPs to prepare Cap-decorated SeNPs (Cap@SeNPs), and the antiproliferative effect and mechanism of Cap@SeNPs in HepG2 were investigated.MethodsCap@SeNPs were prepared through a redox method and characterized using ultraviolet-visible spectroscopy and Fourier transform infrared spectroscopy. Subsequently, the inhibitory rate of Cap@SeNPs on HepG2 cells was determined by the MTT assay. Finally, the antiproliferative mechanism of Cap@SeNPs was explored through analysis of cell cycle, cell viability, reactive oxygen species levels, mitochondrial membrane potential, nuclear morphology, and caspase activity.ResultsOur results revealed that stable and well-dispersed Cap@SeNPs were successfully fabricated, and the optimum mass ratio of sodium selenite to Cap was 1:2. In addition, Cap@SeNPs showed significant antiproliferative effects on HepG2 cells compared with naked SeNPs. Furthermore, Cap@SeNPs inhibited the proliferation of HepG2 cells by elevating total ROS levels, causing nuclear condensation, affecting mitochondrial membrane potential, which in turn influences caspase protease activity and induces apoptosis.ConclusionThis study developed an innovative approach to enhance the value of Cap, demonstrating that Cap@SeNPs hold promise as potential therapeutic agents for cancer treatment.